Renaissance in Database Management: Navigating the Landscape of Candidate Systems. - Gudivada, Venkat N.; Rao, Dhana; Raghavan, Vijay V. (Computer (00189162), 2016)
Big data requirements are motivating new database-management models that can process billions of data requests per second, and established relational models are changing to keep pace. The authors provide practical tools for navigating this shifting product landscape and finding candidate systems that best fit a data manager's application needs.